Controlled synthesis of AgNPs@ZIF-8 composite: Efficient heterogeneous photocatalyst for degradation of methylene blue and congo red. (August 2020) - Chandra, Ramesh; Nath, Mala
Highlights: AgNPs@ZIF-8 composites were synthesized via in situ synthesis of AgNPs and ZIF-8. SEM, TEM and UV-DRS analysis ensured the proper encapsulation of AgNPs within ZIF-8. Encapsulation prevents the immobilization and agglomeration of AgNPs. SZ2 shows enhanced photodegradation efficiency as compared ZIF-8 for MB. SZ2 removes 100 % CR within 40 min. Abstract: Photocatalytic degradation of organic dyes using novel metal based composite materials is one of the most intriguing and sustainable ways to reduce water pollution. Herein, facile synthesis of AgNPs@ZIF-8 via in situ generation of AgNPs and ZIF-8 (Zeolitic Imidazolate Framework) was demonstrated, and composites with different Ag contents (abbreviated as SZ, SZ1, SZ2 SZ3) were well characterized by powder X-ray diffraction (PXRD) pattern, X-ray photoelectron spectroscopy (XPS) and Fourier transform infra-red (FT-IR) spectroscopy. Encapsulation/decoration of AgNPs (particle size: 96 nm in SZ and 17.32 ± 2.35 nm in SZ1 to SZ3) in ZIF-8 matrix has been ensured by TEM and EDX analysis. Brunauer-Emmett-Teller ( BET) adsorption-desorption studies indicate that the surface area of SZ (982 m 2 g −1 ) is less than those of SZ1 to SZ3 (due to the encapsulation of large amount of Ag nanoparticles in SZ). The synthesized composites are thermally stable up to 400 °C in air and nitrogen atmosphere. AgNPs@ZIF-8 exhibited excellent photocatalytic efficiency to degrade organic dyes compared to ZIF-8 due to its large surface area, highly porous and unique synergistic properties. SZ2 degrades off 97.25 % methylene blue (MB) and 100 % congo red (CR) at pH ≥ 7. Further, degraded fragments were analysed by GC–MS and plausible degradation mechanism was discussed.